Anti-Hyperglycemic and Hypolipidemic Effects of Different Aloe vera (Aloe Barbadensis Miller) Extracts in the Management of Obesity and Diabetes - Pothuraju, Ramesh; Kumar Sharma, Raj; Narender Raju, Panjagari (Current Nutrition & Food Science, 2014)
Obesity is associated with many complicated health problems, especially insulin resistance, type-2 diabetes mellitus (T2DM) and other metabolic disorders. Pharmacological treatments for obesity and T2DM with prolonged treatment duration have been losing their effectiveness. As a result, alternative treatments have gained momentum to treat such type of diseases. Now-a-days, research has been focused towards use of different herbs such as Aloe vera for the treatment of metabolic disorders as they have been used since time immemorial in therapies such as Ayruveda and others. Researchers have used various solvents such as water, alcohol, chloroform and methanol to extract the bioactive compounds from Aloe vera. In this paper, an attempt has been made to review the bioactive components of Aloe vera as influenced by extracting solvents and their application in the management of obesity and diabetes in animal and human studies.
Keywords: Aloe vera